Tugas Keluarga dengan Tingkat Depresi pada Lansia - I Ketut Gama; I Gusti Ayu Harini (Jurnal Gema Keperawatan, 2013)
This study aims to determine the correlated between family task execution and the level of elderly depression. This study is nonexperimental with cross sectional approach, with 108 elders that analyzed with statistic spearman rho test. The result of this test shows there are correlated between family and the level of elderly depression with p= 0,000.